2020
DOI: 10.1186/s40249-020-00680-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of household water treatment with chlorine on diarrhea among children under the age of five years in rural areas of Dire Dawa, eastern Ethiopia: a cluster randomized controlled trial

Abstract: Background Diarrheal disease is a leading cause of child mortality and morbidity worldwide. Household water treatment with chlorine significantly reduces morbidity due to waterborne diseases. However, the effect of point-of-use (POU) water treatment in improving the quality of water in areas where POU is not provided free of charge and the effectiveness of home visits in inspiring household members to use POU regularly have not been studied. The objective of this study was to evaluate the effectiveness of drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…Our result suggested a 52% (IRR = 0.48, 0.42, 0.54, P < 0.001) reduction in CHD from home based water treatment households, which is comparable to the ndings of a 48.0% reduction in Zambia [41], but higher than a 36% reduction in Dire Dawa, eastern Ethiopia [42]. It is evidenced that home based water treatment minimizes the risk of recontamination despite the improved water supply system [43][44][45].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our result suggested a 52% (IRR = 0.48, 0.42, 0.54, P < 0.001) reduction in CHD from home based water treatment households, which is comparable to the ndings of a 48.0% reduction in Zambia [41], but higher than a 36% reduction in Dire Dawa, eastern Ethiopia [42]. It is evidenced that home based water treatment minimizes the risk of recontamination despite the improved water supply system [43][44][45].…”
Section: Discussionsupporting
confidence: 64%
“…Likewise, there might be the presence of chlorine-resistant parasitic protozoa such as oocysts of the Cryptosporidium species and cysts of Giardia lamblia [55]. In other parts, discontinuous use of the water treatment product due to the odor and taste of sodium hypochlorite may be a reason for these disparities in magnitude of the reduction [42]. Moreover, the correct and consistent usage of treated water relies almost exclusively on the consumer behavior [43].…”
Section: Discussionmentioning
confidence: 99%
“…26 It should be noted that the chlorine taste and smell of chlorine-based water treatment products are not insurmountable obstacles to its use, particularly if people are encouraged to use it until they grow accustomed to the smell. 27 In the study area, widespread civic disillusionment was seen as leading to the community's failure to sustain safe water practices. Participants raised concerns about the genuineness of the training they are given at different times.…”
Section: Discussionmentioning
confidence: 99%
“…26 It should be noted that the chlorine taste and smell of chlorine-based water treatment products are not insurmountable obstacles to its use, particularly if people are encouraged to use it until they grow accustomed to the smell. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Almost 88% of diarrhea-associated deaths are attributable to unsafe water, inadequate sanitation, and insu cient hygiene [9]. Several studies explore the effect of single and combined water, sanitation, and hygiene (WASH) intervention in the reduce risk of diarrheal morbidity [8, [10][11][12][13][14]. For example, a systematic review for the effect of WASH interventions for acute childhood diarrhea found that various WASH interventions show diarrhea risk reductions between 27% and 53% in children under ve years old, depending on intervention type [11].…”
Section: Introductionmentioning
confidence: 99%